Efforts to Improve the Ability to Read the Qur'an in Early Children through the Application of the Iqra Method - Farhan, Muhamad; Bahruddin, E. (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2023)
The study aimed to reveal efforts to improve the ability to read the Qur'an in early childhood through the application of the Iqra method at tpq an nur, Cibinong District, Bogor Regency. With three research focuses, namely on aspects of planning, implementation, and aspects of the results of increasing children's Al-Qur'an reading abilities. The research method used in this study was the John Elliot model of classroom action research (CAR). There are four stages carried out in this research, namely; planning, implementation, observation, and reflection. The results showed that: 1) at the planning stage, namely the preparation of RPPH in the first cycle 68.16, the second cycle 76.5, and the third cycle 83.83. So overall the preparation of RPPH in cycles I, II, and III increases. 2) The results of the implementation of the learning process in the first cycle 67.7, in the second cycle 76.7, and the third cycle 83.8. So the overall process of implementing learning in cycles I, II and increases. 3) The results on the ability to read the Qur'an Cycle I were only 9 children whose scores were above the KKM and 17 other children had not yet completed, in the cycle, I got an average score of 65.96, in cycle II the children whose grades were above the KKM increased to 18 and 8 other children have not completed, in cycle II got an average score of 72.07, and cycle III there were 25 children whose grades were above the KKM and 1 child who had not yet fulfilled the KKM got an average score of 78.07.